The Relationship Between Time and Birth Mother Satisfaction With Relinquishment. Issue 2 (April 2018) - Madden, Elissa E.; Ryan, Scott; Aguiniga, Donna M.; Killian, Michael; Romanchik, Brenda
Using data from an online survey of 223 birth mothers who had relinquished an infant for adoption during the last 25 years, this analysis examines the influence of the length of time that has passed since relinquishment on birth mothers' satisfaction with their decision to place their child for adoption. Time since relinquishment, age of the respondent, education level, and income had a significant inverse relationship with birth mothers' satisfaction to place their child for adoption. Two variables were predictive of increased satisfaction with their decision: having current contact with the child and full-time employment. The findings underscore the importance of agencies and adoption professionals ensuring that birth mothers have access to ongoing postrelinquishment support services throughout the life course.